Sosialiasi Penunjang Kelancaran Pelayaran Nelayan Purse Seine Kilensari Situbondo - Dyah Silvana Amalia; Winasis Yulianto (GUNAVATTA : Jurnal Pengabdian Masyarakat, 2025)
Purse Seine Ship Fishermen are fishermen who sail using a ship with fishing gear whose main tool is a net, used to catch large fish or small fish according to size and quantity. Fishermen in looking for fish need to be equipped with skills in the field of ship engine maintenance as a vehicle used by fishermen to catch fish and operate fishing gear, especially purse seine. This community service is carried out by providing training and maintenance of one-cylinder boat engines on two fishing boats that are damaged. This activity was attended by all fishermen and received good appreciation, and the community was greatly helped by this training. The results of this training have a good impact on the community. In the evaluation results, the fishermen can repair and maintain their boats independently.